Mechanical properties of anodic titanium dioxide nanostructures - Kulkarni, Mukta; Sepitka, Josef; Junkar, Ita; Bencina, Metka; Rawat, Niharika; Mazare, Anca; Rode, Chandrashekhar; Gokhale, Suresh; Schmuki, Patrik; Daniel, Matej; Iglic, Ales (Materiali in Tehnologije, 2021)
Highly ordered and uniform titanium dioxide (TiO2) nanotubes (NTs) with different morphologies (15 nm, 50 nm and 100 nm in diameter) were prepared by the electrochemical anodization of Ti substrates. The TiO2 NTs' surface properties were characterized by X-ray diffraction (XRD) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). The elastic modulus (E) and the Vickers hardness (HV) of the Ti foil and of the different-morphology TiO2 NTs were evaluated with the nano-indentation technique. E and HV increase with the decreasing length/diameter of the NTs, meaning that NTs with smaller diameters are more resistant to mechanical wear. The elastic modulus of the TiO2 NTs with 15-nm and 50-nm diameters is similar to that of the human bone.
Keywords: Elastic modulus; mechanical properties; titanium dioxide (TiO2) nanotubes; Vickers hardness